2009
DOI: 10.1117/12.817823
|View full text |Cite
|
Sign up to set email alerts
|

Photonic bandgap fiber-enabled Raman detection of nitrogen gas

Abstract: Raman detection of nitrogen gas is very difficult without a multi-pass arrangement and high laser power. Hollow-core photonic bandgap fibers (HC-PBF) provide an excellent means of concentrating light energy in a very small volume and long interaction path between gas and laser. One particular commercial fiber with a core diameter of 4.9 microns offers losses of about 1dB/m for wavelengths between 510 and 610 nm. If 514nm laser is used for excitation, the entire Raman spectrum up to above 3000 cm -1 will be con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…462,463 Advances in direct spectroscopic sensing that do not require a sensing material to generate the signal, are utilizing new physical principles and engineering designs to dramatically reduce the volume of analytical gas cells, improve detection sensitivity, and reduce device size. 464,465 …”
Section: Summary and Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…462,463 Advances in direct spectroscopic sensing that do not require a sensing material to generate the signal, are utilizing new physical principles and engineering designs to dramatically reduce the volume of analytical gas cells, improve detection sensitivity, and reduce device size. 464,465 …”
Section: Summary and Perspectivementioning
confidence: 99%
“…For example, advances in miniaturization and ionization sources in mass spectrometry are bringing micromachined mass spectrometry (MS) devices to the point of operating at ambient atmospheric pressure without vacuum pumps . Advances in miniaturization in ion mobility spectrometry (IMS) are bringing these devices to form factors and power requirements similar to conventional packaged sensor systems. , Advances in miniaturization in gas chromatography are establishing the ability to detect and quantify 10 or more volatiles in <1 min with ppb detection limits in cell-phone-sized microgas analyzers (MGAs). , Advances in direct spectroscopic sensing that do not require a sensing material to generate the signal are utilizing new physical principles and engineering designs to dramatically reduce the volume of analytical gas cells, improve detection sensitivity, and reduce device size. , …”
Section: Summary and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Some provisional tests using Raman scattering of industrial gases trapped in a HC-PCF showed that the concept had great promise. [37][38][39] In this paper, we present the design and test of a simple analyzer for trace gas detection employing Raman scattering and HC-PCF. Using a near-IR optimized, 2.5 m long fiber, we found that a forward scattering measurement configuration leads to a markedly better SNR than a back scattering configuration.…”
Section: Introductionmentioning
confidence: 99%
“…The minimum detectable concentration was ∼15 ppmv determined by measuring the concentration of carbon dioxide gas in ambient air which was notably lower than previous studies that used a HC-PCF optimized for visible wavelengths. 37,39 In addition, some provisional tests on breath samples were conducted. To the best of our knowledge, this is the first reported Raman-based breath analyzer using HC-PCF.…”
Section: Introductionmentioning
confidence: 99%